Evaluating The Effectiveness of a State-Mandated Benchmark Reading Assessment: mCLASS Reading 3D (Text Reading and Comprehension). Issue 4 (19th May 2018) - Snow, Amie B.; Morris, Darrell; Perney, Jan
ABSTRACT: We examined which of two instruments (Text Reading and Comprehension inventory [TRC] or a traditional informal reading inventory [IRI]) provides the more valid assessment of a primary-grade student's reading instructional level. The TRC is currently the required, benchmark reading assessment for students in grades K–3 in the state of North Carolina. The TRC and IRI were administered to 196 students in grades 1–3. Results showed that the TRC, when compared to the IRI, (a) underestimated students' reading instructional level, and (b) took three times as long to administer. Suggestions for improving the instrument are offered.